EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) DENGAN PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK (PMR) PADA POKOK BAHASAN SEGIEMPAT DITINJAU DARI GAYA BELAJAR SISWA SMP NEGERI DI KOTA SALATIGA TAHUN AJARAN 2012/2013 - Sulistiyono, Sulistiyono; Mardiyana, Mardiyana; Sari, Dewi Retno (Jurnal Pembelajaran Matematika, 2013)
ABSTRACT: The aims of the research were to determine the effect of learning models on learning achievement viewed from students’ learning styles. The learning models compared were cooperative learning model Numbered Heads Together (NHT) with Realistic Mathematics Education (RME) approach, Numbered Heads Together (NHT) and conventional. This research was a quasi-experimental research using factorial design of 3x3. The population of the research were all students of the Public Junior High Schools (SMP Negeri) in Salatiga City. The samples of the research were seven grade students of SMP Negeri 2, SMP Negeri 5 and SMP Negeri 7 in Salatiga City (85 students for for first experimental class, 83 students for second experimental class, and 86 students for control class). The samples were chosen by using stratified cluster random sampling. In collecting the data, the instruments used were multiple-choice test of learning achievement in mathematics and student learning style questionnaire. The technique of analyzing the data was unbalanced two-ways Anova. The results of the research are as follows: (1) the cooperative learning model NHT with RME approach and cooperative learning model NHT result in the same good learning achievement in mathematics, and both result in a better learning achievement in mathematics than the conventional learning model; (2) there are no any differences in the learning achievement in mathematics of the students with the visual, auditory, and kinesthetic learning styles; (3) in each learning style, the cooperative learning model NHT with RME approach and cooperative learning model NHT result in the same good learning achievement in mathematics, and both result in a better learning achievement in Mathematics than the conventional learning model; (4) in each learning model, the students with the visual, auditory, and kinesthetic learning styles have the same learning achievement in mathematics. Keywords: cooperative learning, NHT, RME, learning style, learning achievement in mathematics.